Function of Figurative Language Found in Greys Anatomy’s Movie Script - Utari Fatchiyati; Sujana Sujana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
This research aims to identify types of figurative language found in some of Greys Anatomy’s movie scripts and to identify the function of figurative language in some of Greys Anatomy’s movie scripts. The source of the data in this research is the dialogue in Greys Anatomy. To achieve the aims of this research; the researcher uses the qualitative research method. The researcher uses the theory of Kennedy & Perrine. The first result of this research is 100 data can be classified in Figurative Language, 7% Simile, 65% Metaphor, 7% Personification, 4% Hyperbole, 9% Understatement, 3% Metonymy, and 5% Paradox. The second result of this research is 92 data can be categorized as a function of figurative language. 14% Imaginative Pleasure, 13% Additional Imagery, 48% Emotional Intensity, and 25% Means of Concentration.